2021
DOI: 10.3390/foods10030558
|View full text |Cite
|
Sign up to set email alerts
|

An Italian-Mediterranean Dietary Pattern Developed Based on the EAT-Lancet Reference Diet (EAT-IT): A Nutritional Evaluation

Abstract: There is an urgent need to promote healthy and sustainable diets that are tailored to the preferences and cultures of different populations. The present study aimed to (i) define a Mediterranean dietary pattern in line with the EAT-Lancet Commission reference diet (ELCRD), based on 2500 kcal/day and adapted to the Italian food habits (EAT-IT); (ii) develop a mid/long-term dietary plan based on EAT-IT and a dietary plan based on the Italian Dietary Guidelines (IDG); (iii) compare the two dietary plans in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 36 publications
3
54
1
Order By: Relevance
“…As expected from the differences between the two scores for adherence to the Mediterranean diet, we observed high MDS-14 scores among nut consumers (nut consumption questions were included) but no differences in the MEDScore-55 results between groups. Although the EAT-Lancet Commission suggested a higher consumption of nuts compared to that in the healthy Mediterranean style [7], the inclusion of nuts among the proteins from vegetable sources implicates greater energy from lipids [9], as observed in our study. Due to the low score assigned to alcohol consumption, MEDScore-55 can be considered healthier according to the latest national guidelines for nutrition [60], in addition to having a low environmental impact [6].…”
Section: Lifestyle Food Choices and Sustainabilitysupporting
confidence: 52%
See 1 more Smart Citation
“…As expected from the differences between the two scores for adherence to the Mediterranean diet, we observed high MDS-14 scores among nut consumers (nut consumption questions were included) but no differences in the MEDScore-55 results between groups. Although the EAT-Lancet Commission suggested a higher consumption of nuts compared to that in the healthy Mediterranean style [7], the inclusion of nuts among the proteins from vegetable sources implicates greater energy from lipids [9], as observed in our study. Due to the low score assigned to alcohol consumption, MEDScore-55 can be considered healthier according to the latest national guidelines for nutrition [60], in addition to having a low environmental impact [6].…”
Section: Lifestyle Food Choices and Sustainabilitysupporting
confidence: 52%
“…The authors concluded that the consumption of nuts and legumes should be doubled to meet the targets proposed by the EAT-Lancet Commission [8]. However, Tucci et al [9] recently noted that adapting a 2500 kcal/d EAT-Lancet Commission reference diet (ELCRD) to Italian food habits (EAT-IT) would yield considerably higher nut consumption compared with a dietary plan based on the Italian dietary guidelines (IDG) and would present certain nutritional issues due to the higher energy intake from lipids. In a randomized controlled trial among men, the energy intake from a walnut-supplement diet (including 75 g/d of walnuts) exceeded the usual diet, and 86% of the total fat from walnuts was not displaced [10].…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean dietary pattern, being a plant-based diet, can protect the environment from further losses and can therefore play an important role in supporting biodiversity [ 72 ]. With the alarming pace of food biodiversity loss, shifting toward environmentally friendly dietary patterns can be seen as urgently needed [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, EAT-Lancet recommendations have not a prescriptive intent but represent a general model that the Authors reported as a universal healthy diet. Comparison between the recommended portions of the Italian dietary guidelines for healthy eating and the planetary healthy diet adapted to Italian habits was carried out in [ 33 ]. The Italian recommendations suggest a higher amount of fruit and vegetables compared to the planetary healthy diet, while the EAT-Lancet plan was higher in nuts and legumes, which represent the main protein sources.…”
Section: Discussionmentioning
confidence: 99%